2022
DOI: 10.1002/1878-0261.13266
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cellular senescence to combat cancer and ageing

Abstract: Senescence is a complex cellular process that is implicated in various physiological and pathological processes. It is characterized by a stable state of cell growth arrest and by a secretome of diverse pro‐inflammatory factors, chemokines and growth factors. In this review, we summarize the context‐dependent role of cellular senescence in ageing and in age‐related diseases, such as cancer. We discuss current approaches to targeting senescence to develop therapeutic strategies to combat cancer and to promote h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 173 publications
0
6
0
Order By: Relevance
“…These findings may indicate some association between smoking and aging. Cellular senescence includes inflammation, fibrosis, metabolic disorders, DNA damage, mitochondrial dysfunction, loss of protein homeostasis, failed autophagy, Reactive Oxygen Species generation, NAD + depletion, and stem/progenitor cell dysfunction [31][32][33] . A mixture of thousands of chemicals is created by burning or heating tobacco when people smoke.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may indicate some association between smoking and aging. Cellular senescence includes inflammation, fibrosis, metabolic disorders, DNA damage, mitochondrial dysfunction, loss of protein homeostasis, failed autophagy, Reactive Oxygen Species generation, NAD + depletion, and stem/progenitor cell dysfunction [31][32][33] . A mixture of thousands of chemicals is created by burning or heating tobacco when people smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition to a critical threshold length that is no longer able to sustain telomere integrity is one of several known inducers of cellular senescence [50]. This type of senescence, termed telomere-induced or replicative senescence, can be triggered by the well-known tumour suppressor p53 and its downstream effector p21, a cyclin-dependent kinase inhibitor that represses the cell cycle (as discussed in an accompanying article in this special series [51,52]). Mathematical models and studies of budding yeast have suggested that the shortest telomeres are responsible for senescence induction [53,54].…”
Section: Telomere Erosion: a Harbinger Of Senescencementioning
confidence: 99%
“…Senescent cells secret specific small molecules or exosomes (EV) that interact with and influence the nearby environment. This phenomenon is known more generally as the Senescence-Associated Secretory Phenotype (SASP) and is a phenotype common to many senescent states, including that induced by eroded telomeres (please see accompanying review) [51,52,62,65,66] (Fig. 2).…”
Section: Telomere Erosion: a Harbinger Of Senescencementioning
confidence: 99%
“…Senescence-associated proliferation arrest and SASP cooperate in tumor suppression, by arresting proliferation of damaged pre-malignant cells and promoting immune clearance. Although senescence is acutely tumor suppressive, over the longer term, as a source of chronic inflammation, SASP also promotes tissue aging and disease, as reviewed by Rugang Zhang and colleagues [52] and Naoko Ohtani and colleagues [53].…”
Section: Other Potential Causes Of Age-associated Cancermentioning
confidence: 99%